Educational Management Effectiveness in Improving Patient Safety in a Radiology Unit: An Integrated Man, Machine, and Money Approach - Yovana P M Mamesah; Herry Sumual; Tinni Mogea; Joseph Philip Kambey (JR Education, 2026)
Patient safety in radiology requires more than technical compliance; it depends on how a hospital manages human competence, technology-intensive infrastructure, and the financial resources that sustain training and equipment maintenance. This article analyzes the effectiveness of educational management in improving patient safety in a radiology unit through the integrated Man, Machine, and Money framework. The study used a sequential explanatory mixed-methods design. Quantitative data were analyzed with Partial Least Squares Structural Equation Modeling, while qualitative data from interviews, observation, and document review were analyzed thematically to explain and deepen the statistical results. The findings show that human resource competence, facilities and infrastructure management, and financial management are statistically significant determinants of patient safety in radiology. Human competence produced the strongest practical emphasis because staff knowledge, safety training, radiation protection behavior, and adherence to standard operating procedures directly shape safe work performance. Facilities and infrastructure management contributed by ensuring that CT scan, MRI, X-ray, and supporting equipment are maintained, calibrated, and used according to risk-control standards. Financial management influenced patient safety by determining the sustainability of training, maintenance, protective equipment, and monitoring systems, although its statistical coefficient requires contextual interpretation because budget realization was constrained by internal bureaucracy. The qualitative phase revealed persistent barriers: limited continuous training, uneven certification, non-optimal equipment maintenance, insufficient simulation facilities, and delayed budget realization. The article proposes an integrated educational management model based on continuous quality improvement, learning organization principles, and PDCA cycles. The model positions patient safety as the outcome of coordinated development of people, equipment, and accountable financing. The study contributes to educational management in healthcare by demonstrating that patient safety education should be managed as an organizational learning system rather than as isolated training events.